Defect Graphene as a Trifunctional Catalyst for Electrochemical Reactions. Issue 43 (13th September 2016) - Jia, Yi; Zhang, Longzhou; Du, Aijun; Gao, Guoping; Chen, Jun; Yan, Xuecheng; Brown, Christopher L.; Yao, Xiangdong
Abstract : Defects derived by the removal of heteroatoms from graphene are demonstrated, both experimentally and theoretically, to be effective for all three basic electrochemical reactions, e.g., oxygen reduction (ORR), oxygen evolution (OER), and hydrogen evolution (HER). Density function theory calculations further reveal that the different types of defects are essential for the individual electrocatalytic activity for ORR, OER, and HER, respectively.